Responsible marketing and consumption: a teaching experience based on challenges and sustainability as cross-cutting themes - De-Juan-Vigaray, María D; González-Gascón, Elena (Journal of Management and Business Education, 2023)
This study aims to determine whether marketing can be an effective tool to influence society towards responsible consumption while simultaneously contributing to social causes, and teaching higher education students the fundamentals of marketing through various practices implemented during the academic year. Focusing on the Writing Material Recycling Project at the University of Alicante (Spain), the research highlights how this project, initiated in 2014, has promoted sustainability and supported social causes through the recycling of disposable writing materials. The project employs active collaborative learning methodologies based on projects, challenges, action, and service. The results support that this approach has not only contributed to environmental and social causes but has also raised awareness among students about sustainability, helping them acquire skills such as critical thinking, teamwork, and creativity, among others, preparing them for future professional challenges. The study concludes that marketing and the Writing Material Recycling Project can play a crucial role in promoting sustainable consumption, supporting social causes, and educating students in the fundamentals of marketing, while promoting personal development and acquiring new skills among the student body.